Reinforcement film, manufacturing method of device and reinforcement method
Patent Information
- Application Number
- JP2023131281
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025976000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a reinforced film having a film substrate and a photocurable pressure-sensitive adhesive layer bonded together. The present invention also relates to a method for producing a device having a surface to which the reinforced film is bonded, and a reinforcing method for bond-laminating a reinforced film to the surface of an adherend. [Background technology]
[0002] An adhesive film may be attached to the surface of an optical device such as a display or an electronic device for the purpose of surface protection, imparting impact resistance, etc. Such an adhesive film usually has an adhesive layer fixedly laminated on the main surface of a film substrate, and is attached to the device surface via this adhesive layer.
[0003] By temporarily attaching an adhesive film to the surface of a device or device component before use during device assembly, processing, transportation, etc., it is possible to prevent the adherend from being scratched or damaged. Patent Document 1 discloses a reinforcing film provided on a film substrate with a photocurable adhesive layer containing an acrylic-based polymer, a multifunctional (meth)acrylate as a photocuring agent, and a photopolymerization initiator.
[0004] This reinforcing film has low adhesiveness immediately after application to the adherend, making it easy to peel off from the adherend. This allows for reworking from the adherend, and also allows for selective peeling and removal of the reinforcing film from areas of the adherend that do not require reinforcement. The adhesive of the reinforcing film firmly bonds to the adherend upon photocuring, leaving the film substrate permanently bonded to the surface of the adherend, making it usable as a reinforcing material for protecting the surface of devices, etc. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2022 / 050009 Summary of the Invention [Problem to be solved by the invention]
[0006] The reinforcing film to be attached to the surface of a device is required to have high adhesive strength after the adhesive layer is photocured, and not peel off from the adherend even when the device is deformed by bending or the temperature changes. Patent Document 1 describes that by using an acrylic polymer with a low glass transition temperature as the base polymer constituting the photocurable adhesive, the adhesive layer has a low storage modulus and high stress-strain relaxation property, so that peeling of the adhesive layer at bending points of the device is suppressed and adhesive reliability is excellent.
[0007] However, when the reinforced film disclosed in Patent Document 1 is attached to a flexible device using a film substrate and a temperature cycle test is performed in which the temperature is changed from low to high and back again, the device may warp or the reinforced film may peel off. In view of this problem, the present invention aims to provide a reinforced film that is less likely to warp the adherend or cause the reinforced film to peel off from the adherend, even when the temperature is repeatedly changed between low and high temperatures. [Means for solving the problem]
[0008] The reinforcing film of the present invention includes a pressure-sensitive adhesive layer bonded to one main surface of a film substrate, the pressure-sensitive adhesive layer comprising a photocurable composition containing an acrylic-based polymer having a crosslinked structure, a photocuring agent, and a photopolymerization initiator.
[0009] The acrylic base polymer is made of (meth)acrylic acid C, whose alkyl group has 6 to 9 carbon atoms, as a monomer component. 6-9 Alkyl esters, (meth)acrylic acid C with alkyl groups having 10 to 20 carbon atoms 10-20 The monomer component contains at least one selected from the group consisting of alkyl esters, hydroxyl group-containing monomers, and carboxyl group-containing monomers. 6-9The amount of alkyl ester is 40 parts by weight or more. 10-20 The amount of alkyl ester may be 1 to 40 parts by weight.
[0010] A crosslinked structure is introduced into the acrylic base polymer. The crosslinked structure is preferably introduced using 0.05 to 1.0 parts by weight of a crosslinking agent per 100 parts by weight of the polymer. Examples of crosslinking agents include isocyanate-based crosslinking agents and epoxy-based crosslinking agents.
[0011] The photocurable composition constituting the pressure-sensitive adhesive layer contains, as a photocuring agent, a polyfunctional (meth)acrylate having no urethane bond and a urethane (meth)acrylate. The amount of the polyfunctional (meth)acrylate having no urethane bond is preferably 2 to 25 parts by weight per 100 parts by weight of the acrylic base polymer. The amount of the urethane (meth)acrylate is preferably 0.03 to 5 parts by weight per 100 parts by weight of the acrylic base polymer.
[0012] The polyfunctional (meth)acrylate having no urethane bond may have a functional group equivalent of a (meth)acryloyl group of 80 to 500 g / eq. The urethane (meth)acrylate may have a functional group equivalent of a (meth)acryloyl group of 80 to 5000 g / eq. The urethane (meth)acrylate may have four or more (meth)acryloyl groups in one molecule.
[0013] Before photocuring, the adhesive layer preferably has an adhesive strength F0 to a polyimide film of 0.6 N / 25 mm or less at 25°C. After photocuring, the adhesive layer preferably has an adhesive strength F1 to a polyimide film of 3.0 N / 25 mm or more at 25°C and an adhesive strength F2 to a polyimide film of 1.0 N / 25 mm or more at 85°C.
[0014] The pressure-sensitive adhesive layer after photocuring preferably has a shear storage modulus of 100 kPa or less at a temperature of 25°C, and a shear storage modulus of 1000 kPa or less at a temperature of -40°C.
[0015] The above-mentioned reinforcing film is temporarily attached to the surface of a device as an adherend, and then the pressure-sensitive adhesive layer is photocured to obtain a device with the reinforcing film. The device may be a foldable flexible device, and the adherend (reinforcement target) of the reinforcing film may be a foldable image display element.
[0016] After the reinforcing film is temporarily attached to the adherend, and before the adhesive layer is photocured, the reinforcing film temporarily attached to the adherend may be cut and peeled off from a portion of the adherend (a non-reinforced area). [Effects of the Invention]
[0017] The reinforcing film of the present invention has a pressure-sensitive adhesive layer made of a photocurable composition, and by photocuring the pressure-sensitive adhesive layer after adhering to the adherend, the adhesive strength with the adherend is increased. Before photocuring, the pressure-sensitive adhesive layer has low adhesive strength to the adherend and is easy to peel from the adherend. After photocuring, the pressure-sensitive adhesive has high adhesive strength even at high temperatures and exhibits little change in shear storage modulus with temperature change, so that warping of the adherend and peeling of the reinforcing film from the adherend are unlikely to occur even when the temperature is repeatedly changed between low and high temperatures. [Brief explanation of the drawings]
[0018] [Figure 1] FIG. 2 is a cross-sectional view showing a laminated structure of a reinforcing film. [Figure 2] FIG. 2 is a cross-sectional view showing a laminated structure of a reinforcing film. [Figure 3] FIG. 10 is a cross-sectional view showing a device to which a reinforcing film is attached. DETAILED DESCRIPTION OF THE INVENTION
[0019] 1 is a cross-sectional view showing one embodiment of a reinforced film. Reinforced film 10 has a pressure-sensitive adhesive layer 2 on one main surface of a film substrate 1. The pressure-sensitive adhesive layer 2 is fixedly laminated on one main surface of the film substrate 1. The pressure-sensitive adhesive layer 2 is a photocurable pressure-sensitive adhesive made from a photocurable composition, and is cured by irradiation with actinic rays such as ultraviolet light, thereby increasing the adhesive strength with an adherend.
[0020] Fig. 2 is a cross-sectional view of a reinforced film having a release liner 5 temporarily attached onto the main surface of a pressure-sensitive adhesive layer 2. Fig. 3 is a cross-sectional view showing a state in which a reinforced film 10 is attached to the surface of a device 20.
[0021] The release liner 5 is peeled off and removed from the surface of the adhesive layer 2, and the exposed surface of the adhesive layer 2 is attached to the surface of the device 20, thereby attaching the reinforcement film 10 to the surface of the device 20. In this state, the adhesive layer 2 has not yet been photocured, and the reinforcement film 10 (adhesive layer 2) is temporarily attached to the device 20. By photocuring the adhesive layer 2, the adhesive strength at the interface between the device 20 and the adhesive layer 2 increases, and the device 20 and the reinforcement film 10 are fixed together.
[0022] "Fixed" means that the two laminated layers are firmly bonded together, making it difficult or impossible to separate them at their interface. "Temporary adhesion" means that the adhesive strength between the two laminated layers is weak, making them easy to separate at their interface.
[0023] In the reinforced film shown in Figure 2, film substrate 1 and pressure-sensitive adhesive layer 2 are bonded together, and release liner 5 is temporarily attached to pressure-sensitive adhesive layer 2. When film substrate 1 and release liner 5 are peeled apart, peeling occurs at the interface between pressure-sensitive adhesive layer 2 and release liner 5, and the pressure-sensitive adhesive layer 2 remains bonded to film substrate 1. No pressure-sensitive adhesive remains on release liner 5 after peeling.
[0024] In the device with the reinforcement film 10 attached shown in FIG. 3, the device 20 and the adhesive layer 2 are in a temporarily bonded state before the adhesive layer 2 is photocured. When the film substrate 1 is peeled from the device 20, peeling occurs at the interface between the adhesive layer 2 and the device 20, and the adhesive layer 2 remains adhered to the film substrate 1. Since no adhesive remains on the device 20, rework is easy. After the adhesive layer 2 is photocured, the adhesive strength between the adhesive layer 2 and the device 20 increases, making it difficult to peel the reinforcement film 10 from the device 20, and peeling the two may cause cohesive failure of the adhesive layer 2.
[0025] [Structure of the reinforcing film] <Film substrate> A plastic film is used as the film substrate 1. In order to bond the film substrate 1 and the pressure-sensitive adhesive layer 2 together, it is preferable that the surface of the film substrate 1 to which the pressure-sensitive adhesive layer 2 is to be attached is not subjected to a release treatment.
[0026] The thickness of the film substrate 1 is, for example, about 4 to 500 μm. From the viewpoint of reinforcing the device by imparting rigidity and cushioning impact, the thickness of the film substrate 1 is preferably 12 μm or more, more preferably 30 μm or more, and even more preferably 45 μm or more. From the viewpoint of imparting flexibility to the reinforcing film to improve handleability, the thickness of the film substrate 1 is preferably 300 μm or less, and more preferably 200 μm or less. To impart flexibility to the reinforcing film to make it foldable, the thickness of the film substrate 1 is preferably 125 μm or less, and more preferably 100 μm or less. From the viewpoint of achieving both mechanical strength and flexibility, the compressive strength of the film substrate 1 is 100 to 3000 kg / cm 2 is preferred, and 200 to 2900 kg / cm 2 More preferably, 300 to 2800 kg / cm 2 is more preferably 400 to 2700 kg / cm 2 is particularly preferred.
[0027] Examples of plastic materials constituting the film substrate 1 include polyester resins, polyolefin resins, cyclic polyolefin resins, polyamide resins, polyimide resins, and polyether ether ketone resins. In a reinforcement film for an optical device such as a display, the film substrate 1 is preferably a transparent film. Furthermore, when photocuring of the pressure-sensitive adhesive layer 2 is performed by irradiating actinic rays from the film substrate 1 side, the film substrate 1 is preferably transparent to the actinic rays used to cure the pressure-sensitive adhesive layer. Polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate are preferably used because they combine mechanical strength and transparency. When irradiating actinic rays from the adherend side to cure the pressure-sensitive adhesive layer, the adherend only needs to be transparent to actinic rays, and the film substrate 1 does not need to be transparent to actinic rays.
[0028] The surface of the film substrate 1 may be provided with a functional coating such as an easy-adhesion layer, an easy-slip layer, a release layer, an antistatic layer, a hard coat layer, or an antireflection layer. As described above, in order to bond the film substrate 1 and the pressure-sensitive adhesive layer 2 together, it is preferable that no release layer is provided on the surface of the film substrate 1 to which the pressure-sensitive adhesive layer 2 is to be attached.
[0029] <Adhesive layer> The adhesive layer 2, which is adhered and laminated onto the film substrate 1, is made of a photocurable composition containing a base polymer, a photocuring agent, and a photopolymerization initiator. Before photocuring, the adhesive layer 2 has low adhesive strength to adherends such as devices and device components, making it easy to peel off. The adhesive layer 2's adhesive strength to adherends improves upon photocuring, making it difficult for the reinforcing film to peel off from the device surface even when the device is in use, resulting in excellent adhesive reliability.
[0030] Photocurable pressure-sensitive adhesives hardly cure under normal storage conditions, but cure when exposed to actinic rays such as ultraviolet rays. Therefore, the reinforcing film of the present invention has the advantage that the timing of curing of the pressure-sensitive adhesive layer 2 can be set as desired, allowing for flexible adaptation to process lead times, etc.
[0031] The thickness of the pressure-sensitive adhesive layer 2 is, for example, about 1 to 300 μm. The thicker the pressure-sensitive adhesive layer 2, the more the adhesive strength to the adherend tends to improve. On the other hand, if the pressure-sensitive adhesive layer 2 is excessively thick, the fluidity before photocuring may be high, making handling difficult. Therefore, the thickness of the pressure-sensitive adhesive layer 2 is preferably 3 to 100 μm, more preferably 5 to 50 μm, even more preferably 6 to 40 μm, and particularly preferably 8 to 30 μm. From the viewpoint of achieving a thinner thickness, the thickness of the pressure-sensitive adhesive layer 2 may be 25 μm or less, 20 μm or less, or 18 μm or less.
[0032] When the reinforcing film is used in an optical device such as a display, the total light transmittance of the pressure-sensitive adhesive layer 2 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The haze of the pressure-sensitive adhesive layer 2 is preferably 2% or less, more preferably 1% or less, even more preferably 0.7% or less, and particularly preferably 0.5% or less.
[0033] In the following, preferred embodiments of each component of the photocurable composition that constitutes the pressure-sensitive adhesive layer 2 will be explained in order.
[0034] (base polymer) The base polymer is the main component of the pressure-sensitive adhesive composition and is the main factor determining the adhesive strength of the pressure-sensitive adhesive layer. The pressure-sensitive adhesive composition contains an acrylic polymer as the base polymer. It is preferable that 50% by weight or more of the pressure-sensitive adhesive composition is an acrylic polymer. The acrylic base polymer has excellent optical transparency and adhesive properties, and the adhesive strength can be easily controlled.
[0035] The acrylic polymer preferably contains an alkyl (meth)acrylate ester as a main monomer component. In this specification, "(meth)acrylic" means acrylic and / or methacrylic.
[0036] As the (meth)acrylic acid alkyl ester, a (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20 is preferably used. The (meth)acrylic acid alkyl ester may have a branched alkyl group or may have a cyclic alkyl group (alicyclic alkyl group).
[0037] Specific examples of the (meth)acrylic acid alkyl ester having a chain alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, and (meth) Examples of the acrylate include nonyl acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.
[0038] Specific examples of (meth)acrylic acid alkyl esters having an alicyclic alkyl group include (meth)acrylic acid cycloalkyl esters such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylic acid esters having a bicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; and (meth)acrylic acid esters having a tricyclic or higher aliphatic hydrocarbon ring such as dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate. The (meth)acrylic acid alkyl esters having an alicyclic alkyl group may have a substituent on the ring, such as 3,3,5-trimethylcyclohexyl (meth)acrylate. The (meth)acrylic acid alkyl ester having an alicyclic alkyl group may also be a (meth)acrylic acid ester containing a condensed ring of an alicyclic structure and a ring structure having an unsaturated bond, such as dicyclopentenyl (meth)acrylate.
[0039] The content of the (meth)acrylic acid alkyl ester is preferably 50 parts by weight or more, more preferably 60 parts by weight or more, and may be 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, or 95 parts by weight or more, relative to 100 parts by weight of the total amount of the monomer components constituting the polymer.
[0040] In order to lower the glass transition temperature (Tg) of the acrylic base polymer and increase adhesive strength over a wide temperature range, the alkyl group of the (meth)acrylic acid alkyl ester is preferably a chain alkyl group, which may be linear or branched.
[0041] In the present invention, the acrylic base polymer contains, as a monomer component, (meth)acrylic acid C 1 having an alkyl group with 6 to 9 carbon atoms. 6-9 Alkyl esters and (meth)acrylic acids C in which the alkyl group has 10 to 20 carbon atoms10-20 Contains alkyl esters.
[0042] (Meth)acrylic acid C 6-9 Since the glass transition temperature (Tg) of the homopolymer of alkyl ester is low, the acrylic base polymer is made of (meth)acrylic acid C as a monomer component. 6-9 By including alkyl ester, the Tg of the acrylic base polymer is lowered. 6-9 Among alkyl esters, those having a homopolymer glass transition temperature of -50°C or less are preferred.
[0043] (Meth)acrylic acid C, the glass transition temperature of which homopolymer is -50°C or less 6-9 Specific examples of alkyl esters include 2-ethylhexyl acrylate (Tg: -70°C), n-hexyl acrylate (Tg: -65°C), n-octyl acrylate (Tg: -65°C), isononyl acrylate (Tg: -60°C), n-nonyl acrylate (Tg: -58°C), isooctyl acrylate (Tg: -58°C), etc. Among these, 2-ethylhexyl acrylate and n-octyl acrylate are preferred because they have a low Tg and can provide a pressure-sensitive adhesive with a low storage modulus.
[0044] The most abundant monomer (main monomer) in the acrylic base polymer is (meth)acrylic acid C 6-9 Preferably, it is an alkyl ester. (Meth)acrylic acid C 6-9 The amount of alkyl ester is preferably 40 parts by weight or more, more preferably 50 parts by weight or more, and may be 55 parts by weight or more, 60 parts by weight or more, or 65 parts by weight or more, relative to 100 parts by weight of the total amount of the constituent monomer components of the polymer.
[0045] (Meth)acrylic acid C 10-20 Alkyl ester homopolymers have a temperature range (plateau region) above Tg where the temperature dependence of viscoelasticity is small. Therefore, when the base polymer contains (meth)acrylic acid C as a monomer component, 10-20By including an alkyl ester, the temperature dependency of the storage modulus is reduced, which may prevent the adherend from warping due to temperature changes and the reinforcing film from peeling off from the adherend.
[0046] Since the temperature range of the plateau region is wide and the storage modulus in the plateau region is small, (meth)acrylic acid C 10-20 Among the chain alkyl esters, (meth)acrylic acid C 12-18 Alkyl esters are preferred, among which dodecyl (meth)acrylate and isostearyl (meth)acrylate are preferred, and dodecyl acrylate (lauryl acrylate) is particularly preferred.
[0047] (Meth)acrylic acid C 10-20 The amount of alkyl ester is preferably 1 to 40 parts by weight, more preferably 2 to 30 parts by weight, and even more preferably 3 to 25 parts by weight, and may be 4 to 20 parts by weight or 5 to 15 parts by weight, relative to 100 parts by weight of the total amount of the constituent monomer components of the polymer.
[0048] The acrylic base polymer contains (meth)acrylic acid C as a monomer component. 6-9 Alkyl esters and (meth)acrylic acid C 10-20 The (meth)acrylic acid alkyl ester may contain an alkyl ester other than the alkyl ester. Examples of the (meth)acrylic acid alkyl ester other than the above include (meth)acrylic acid C alkyl esters such as butyl acrylate. 1-5 Alkyl esters are preferred.
[0049] The acrylic base polymer contains, as constituent monomer components, a hydroxy group-containing monomer and / or a carboxy group-containing monomer in addition to a (meth)acrylic acid alkyl ester. The hydroxy group or carboxy group of the base polymer serves as a reaction site with the crosslinking agent described below. For example, when an isocyanate-based crosslinking agent is used, it is preferable that the base polymer contains a hydroxy group-containing monomer as a monomer component. When an epoxy-based crosslinking agent is used, it is preferable that the base polymer contains a carboxy group-containing monomer as a monomer component. The introduction of a crosslinked structure into the base polymer improves cohesive strength, which tends to improve the releasability of the pressure-sensitive adhesive layer 2 from the adherend before photocuring.
[0050] Examples of hydroxy group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, 4-(hydroxymethyl)cyclohexylmethyl (meth)acrylate, etc. Among these, 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate are preferred because they contribute significantly to improving the adhesive strength of the pressure-sensitive adhesive after photocuring.
[0051] Examples of the carboxy group-containing monomer include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Among these, acrylic acid and methacrylic acid are preferred, with acrylic acid being particularly preferred, since they tend to increase the cohesiveness of the pressure-sensitive adhesive, thereby improving the adhesive strength and adhesive retention.
[0052] From the viewpoint of appropriately introducing a crosslinked structure using a crosslinking agent such as an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent, the total amount of the hydroxy group-containing monomer and the carboxy group-containing monomer relative to 100 parts by weight of the total amount of the constituent monomer components of the acrylic base polymer is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and may be 0.7 parts by weight or more, or 1.0 part by weight or more.
[0053] Because hydroxyl groups and carboxyl groups are highly polar, when the amount of hydroxyl group-containing monomer or carboxyl group-containing monomer in the constituent monomer components of the acrylic base polymer is large, the cohesive strength of the polymer increases, and the storage modulus of the pressure-sensitive adhesive layer after photocuring tends to increase. From the viewpoint of achieving a low storage modulus of the pressure-sensitive adhesive layer 2, the total amount of the hydroxyl group-containing monomer and carboxyl group-containing monomer per 100 parts by weight of the total amount of the constituent monomer components of the acrylic base polymer is preferably 20 parts by weight or less, more preferably 15 parts by weight or less, even more preferably 10 parts by weight or less, and may be 7 parts by weight or less, or 5 parts by weight or less.
[0054] The acrylic base polymer may contain a nitrogen atom-containing monomer as a constituent monomer component. Nitrogen atom-containing monomers have high polarity and cohesive strength, and the glass transition temperature of their homopolymers is high. Therefore, when the acrylic base polymer contains a nitrogen atom-containing monomer as a monomer component, the adhesive strength of the pressure-sensitive adhesive layer after photocuring at high temperatures tends to be improved.
[0055] Examples of the nitrogen atom-containing monomer include N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-acryloylmorpholine, N-vinylcarboxylic acid amides, N-vinylcaprolactam, etc. Among these, N-vinylpyrrolidone is particularly preferred because it has high cohesive strength and contributes greatly to improving adhesive strength at high temperatures.
[0056] When the acrylic base polymer contains a nitrogen atom-containing monomer as a monomer component, from the viewpoint of improving the adhesive strength of the pressure-sensitive adhesive layer at high temperatures after photocuring, the amount of the nitrogen atom-containing monomer is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and may be 0.7 parts by weight or more, relative to 100 parts by weight of the total amount of the constituent monomer components of the polymer. Even a small amount of the nitrogen atom-containing monomer can contribute to improving the adhesive strength at high temperatures.
[0057] When the amount of nitrogen-atom-containing monomer in the constituent monomer components of the acrylic base polymer is high, the cohesive strength of the base polymer tends to be high and the glass transition temperature of the pressure-sensitive adhesive layer tends to be high, and as a result, the storage modulus of the pressure-sensitive adhesive layer after photocuring tends to be high. Furthermore, when the amount of nitrogen-atom-containing monomer is high, the adhesive strength of the pressure-sensitive adhesive layer 2 before photocuring tends to be high, making it difficult to peel the reinforcing film from the adherend. From the viewpoint of reducing the adhesive strength of the pressure-sensitive adhesive before photocuring and reducing the storage modulus of the pressure-sensitive adhesive after photocuring, the amount of nitrogen-atom-containing monomer per 100 parts by weight of the total amount of the constituent monomer components of the acrylic base polymer is preferably 10 parts by weight or less, more preferably 7 parts by weight or less, and may be 5 parts by weight or less, or 3 parts by weight or less.
[0058] The acrylic base polymer may contain other monomer components, such as vinyl ester monomers, aromatic vinyl monomers, epoxy group-containing monomers, vinyl ether monomers, sulfo group-containing monomers, phosphate group-containing monomers, and acid anhydride group-containing monomers.
[0059] From the viewpoint of imparting excellent adhesive properties to the PSA, the glass transition temperature of the acrylic base polymer is preferably −30° C. or lower, more preferably −40° C. or lower, even more preferably −50° C. or lower, and may be −55° C. or lower or −60° C. or lower. The glass transition temperature of the acrylic base polymer is generally −100° C. or higher, and may be −80° C. or higher or −70° C. or higher.
[0060] The glass transition temperature (Tg) is the temperature (peak top temperature) at which the loss tangent tanδ in viscoelasticity measurement is maximized. The theoretical glass transition temperature may be used instead of the glass transition temperature determined by viscoelasticity measurement. The theoretical Tg is the glass transition temperature Tg of a homopolymer of the constituent monomer components of a polymer. i and the weight fraction W of each monomer component i It is calculated using the following Fox formula: 1 / Tg=Σ(W i / Tg i )
[0061] Tg is the theoretical glass transition temperature of the polymer (unit: K), W i is the weight fraction of monomer component i (copolymerization ratio by weight), Tg i is the glass transition temperature (unit: K) of the homopolymer of monomer component i. The glass transition temperature of the homopolymer can be determined from the values listed in Polymer Handbook, 3rd Edition (John Wiley & Sons, Inc., 1989). The glass transition temperature of the homopolymer of a monomer not listed in the above literature can be determined from the peak top temperature of tan δ measured by dynamic viscoelasticity measurement.
[0062] The above monomer components are polymerized by various known methods such as solution polymerization, emulsion polymerization, and bulk polymerization to obtain an acrylic polymer as a base polymer. Solution polymerization is preferred from the viewpoints of cost and the balance of adhesive strength, holding power, and other properties of the pressure-sensitive adhesive. Ethyl acetate, toluene, etc. are used as the solvent for solution polymerization. The solution concentration is usually about 20 to 80% by weight. Various known polymerization initiators such as azo-based and peroxide-based initiators can be used for solution polymerization. A chain transfer agent may be used to adjust the molecular weight. The reaction temperature is usually about 50 to 80°C, and the reaction time is usually about 1 to 8 hours.
[0063] The weight-average molecular weight of the acrylic base polymer is preferably 200,000 or more, more preferably 300,000 or more, and even more preferably 500,000 or more. The higher the weight-average molecular weight of the base polymer, the higher the adhesive strength at high temperatures tends to be. The weight-average molecular weight of the acrylic base polymer may be 1,000,000 or more, 1,300,000 or more, 1,500,000 or more, 1,600,000 or more, or 1,700,000 or more.
[0064] If the weight-average molecular weight of the base polymer is too large, the storage modulus of the PSA tends to be high, and the adhesive strength and flexibility tend to be reduced. Therefore, the weight-average molecular weight of the acrylic base polymer is preferably 3 million or less, more preferably 2.5 million or less, and may be 2.2 million or less or 2 million or less. When a crosslinked structure is introduced into the base polymer, the molecular weight of the base polymer refers to the molecular weight before the crosslinked structure is introduced.
[0065] (Crosslinking agent) It is preferable to introduce a crosslinked structure into the base polymer in order to provide the pressure-sensitive adhesive with an appropriate cohesive strength, thereby developing adhesive strength, and ensuring the peelability of the pressure-sensitive adhesive layer from the adherend before photocuring. For example, the crosslinked structure is introduced by adding a crosslinking agent to a solution obtained by polymerizing the base polymer and heating it as necessary. The crosslinking agent has two or more crosslinkable functional groups per molecule. The crosslinking agent may also have three or more crosslinkable functional groups per molecule.
[0066] Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, carbodiimide-based crosslinking agents, and metal chelate-based crosslinking agents. These crosslinking agents react with functional groups such as hydroxy groups and carboxy groups introduced into the acrylic base polymer to form a crosslinked structure. Isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred because they have high reactivity with the hydroxy groups and carboxy groups of the acrylic base polymer and allow for easy introduction of a crosslinked structure.
[0067] As the isocyanate-based crosslinking agent, a polyisocyanate having two or more isocyanate groups per molecule is used. The isocyanate-based crosslinking agent may be one having three or more isocyanate groups per molecule. Examples of the isocyanate-based crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate and xylylene diisocyanate; trimethylolpropane / trilene diisocyanate; Examples of suitable isocyanate crosslinking agents include isocyanate adducts such as a diisocyanate trimer adduct (e.g., "Takenate D101E" manufactured by Mitsui Chemicals), a trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., "Coronate HL" manufactured by Tosoh), a trimethylolpropane adduct of xylylene diisocyanate (e.g., "Takenate D110N" manufactured by Mitsui Chemicals), and an isocyanurate of hexamethylene diisocyanate (e.g., "Coronate HX" manufactured by Tosoh). Examples of suitable isocyanate crosslinking agents include isocyanate compounds having a biuret group (e.g., "Duranate 24A-100" manufactured by Asahi Kasei) and isocyanate compounds having an allophanate group.
[0068] The epoxy crosslinking agent is a multifunctional epoxy compound having two or more epoxy groups in one molecule. The epoxy crosslinking agent may have three or more or four or more epoxy groups in one molecule. The epoxy group of the epoxy crosslinking agent may be a glycidyl group. Examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, and bisphenol-S-diglycidyl ether. As the epoxy-based crosslinking agent, commercially available products such as "Denacol" manufactured by Nagase ChemteX, and "Tetrad X" and "Tetrad C" manufactured by Mitsubishi Gas Chemical may be used.
[0069] The amount of crosslinking agent used can be adjusted appropriately depending on the composition and molecular weight of the acrylic base polymer, and is preferably about 0.01 to 3 parts by weight per 100 parts by weight of the acrylic base polymer. The greater the amount of crosslinking agent, the higher the crosslink density of the base polymer, imparting appropriate hardness to the pressure-sensitive adhesive layer before photocuring, increasing the storage modulus, and tending to reduce adhesive residue on the adherend when the reinforcement film is peeled from the adherend. On the other hand, if the amount of crosslinking agent is excessively large, the adhesive strength of the pressure-sensitive adhesive layer after photocuring tends to decrease, particularly at high temperatures. Furthermore, if the amount of crosslinking agent is large, the storage modulus of the pressure-sensitive adhesive layer after photocuring tends to increase at low temperatures, which may cause warping of the adherend due to temperature changes or peeling of the reinforcement film from the adherend. In order to achieve both low adhesive strength (easy peelability) of the adhesive layer before photocuring and high adhesive strength of the adhesive layer after photocuring, and to reduce the storage modulus, the amount of crosslinking agent is more preferably 0.05 to 1.0 parts by weight, even more preferably 0.1 to 0.7 parts by weight, and may also be 0.15 to 0.6 parts by weight, 0.2 to 0.5 parts by weight, or 0.25 to 0.4 parts by weight, per 100 parts by weight of the acrylic base polymer.
[0070] (light curing agent) The adhesive composition constituting the adhesive layer 2 contains, in addition to a base polymer, a compound having two or more photopolymerizable functional groups per molecule as a photocuring agent. An adhesive composition containing a photocuring agent has photocurability, and when photocuring is performed after lamination with an adherend, the adhesive strength with the adherend is improved.
[0071] From the viewpoint of compatibility with the base polymer, the photocuring agent is preferably a liquid at room temperature. The photopolymerizable functional group of the photocuring agent is preferably one that is polymerizable by a photoradical reaction. The photocuring agent is preferably a compound having two or more ethylenically unsaturated bonds in one molecule, and polyfunctional (meth)acrylates are preferred because they exhibit appropriate compatibility with the acrylic base polymer.
[0072] In the present invention, a polyfunctional (meth)acrylate having no urethane bond and a polyfunctional (meth)acrylate having a urethane bond are used in combination as the photocuring agent. That is, the photocurable composition constituting the pressure-sensitive adhesive layer 2 contains a polyfunctional (meth)acrylate having no urethane bond and a polyfunctional (meth)acrylate having a urethane bond. Hereinafter, a polyfunctional (meth)acrylate having a urethane bond will be referred to as a "urethane (meth)acrylate." Furthermore, a polyfunctional (meth)acrylate having no urethane bond may be simply referred to as a "polyfunctional (meth)acrylate."
[0073] Examples of polyfunctional (meth)acrylates that do not have a urethane bond include compounds having (meth)acryloyl groups at both ends of a polyalkylene oxide chain, such as polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate; esters of polyols and (meth)acrylic acid, such as bisphenol A di(meth)acrylate, alkanediol di(meth)acrylate, glycerin di(meth)acrylate, glycerin tri(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, isocyanuric acid tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol poly(meth)acrylate; and epoxy (meth)acrylate.
[0074] The polyfunctional (meth)acrylate having no urethane bond may be an ester of an alkylene oxide-modified polyol and (meth)acrylic acid. Examples of the ester of an alkylene oxide-modified polyol and (meth)acrylic acid include bisphenol A alkylene oxide-modified di(meth)acrylate, isocyanuric acid alkylene oxide-modified tri(meth)acrylate, trimethylolpropane alkylene oxide-modified tri(meth)acrylate, pentaerythritol alkylene oxide-modified di(meth)acrylate, pentaerythritol alkylene oxide-modified tri(meth)acrylate, and dipentaerythritol alkylene oxide-modified poly(meth)acrylate.
[0075] Among the above, polyfunctional (meth)acrylates having an alkylene oxide chain are preferred from the viewpoint of reducing the adhesive strength of the pressure-sensitive adhesive layer before photocuring to facilitate peeling and increasing the adhesive strength of the pressure-sensitive adhesive layer after photocuring. Examples of polyfunctional (meth)acrylates having an alkylene oxide chain include compounds having (meth)acryloyl groups at both ends of a polyalkylene oxide chain, such as polyethylene glycol di(meth)acrylate and polypropylene glycol di(meth)acrylate, and esters of alkylene oxide-modified polyols and (meth)acrylic acid.
[0076] In polyfunctional (meth)acrylates containing alkylene oxide chains, the alkylene oxide is preferably (poly)ethylene oxide or (poly)propylene oxide, with (poly)ethylene oxide being particularly preferred. The chain length of the alkylene oxide (the number of repeating units of the alkylene oxide) n is approximately 1 to 15. When multiple alkylene oxide chains are contained in one molecule, the average chain length n is preferably 1 to 15. The (average) chain length n of the alkylene oxide chain may be 12 or less, 10 or less, 8 or less, 6 or less, 5 or less, 4 or less, or 3 or less. Compatibility with the acrylic base polymer can be adjusted by adjusting the type and chain length of the alkylene oxide.
[0077] The alkylene oxide is preferably (poly)ethylene oxide or (poly)propylene oxide, and the chain length (number of repeating units: n) of the alkylene oxide is preferably about 1 to 15. When multiple alkylene oxide chains are contained in one molecule, the average chain length n is preferably 1 to 15. The (average) chain length n of the alkylene oxide chain may be 12 or less, 10 or less, 8 or less, 6 or less, 5 or less, 4 or less, or 3 or less. By adjusting the type and chain length of the alkylene oxide, the compatibility with the acrylic base polymer can be adjusted.
[0078] As the photocuring agent, two or more types of polyfunctional (meth)acrylates having no urethane bond may be used in combination. For example, a polyfunctional (meth)acrylate having relatively low compatibility with acrylic base polymers may be used in combination with a polyfunctional (meth)acrylate having relatively high compatibility with acrylic base polymers. For example, a polyfunctional (meth)acrylate having no alkylene oxide chain has higher compatibility with acrylic base polymers than a polyfunctional (meth)acrylate having an alkylene oxide chain.
[0079] From the viewpoint of compatibility with the acrylic base polymer, the molecular weight of the polyfunctional (meth)acrylate used as the photocuring agent is preferably 1500 or less, more preferably 1000 or less, and may be 800 or less, 500 or less, or 400 or less. From the viewpoint of achieving both compatibility with the acrylic base polymer and improved adhesive strength after photocuring, the functional group equivalent (g / eq) of the polyfunctional (meth)acrylate is preferably 500 or less, more preferably 400 or less, even more preferably 300 or less, particularly preferably 200 or less, and may be 180 or less or 160 or less.
[0080] On the other hand, if the functional group equivalent weight of the polyfunctional (meth)acrylate is too small, the crosslinking density of the pressure-sensitive adhesive layer after photocuring may increase, resulting in reduced adhesiveness. Therefore, the functional group equivalent weight of the polyfunctional (meth)acrylate is preferably 80 or more, more preferably 100 or more, and may be 120 or more or 130 or more.
[0081] By including a polyfunctional (meth)acrylate having an alkylene oxide chain and a urethane (meth)acrylate as a photocuring agent, the adhesive strength (initial adhesive strength) of the pressure-sensitive adhesive layer before photocuring tends to be small. Furthermore, by including a urethane (meth)acrylate as a photocuring agent, the adhesive strength, particularly the adhesive strength at high temperatures, can be increased without excessively increasing the storage modulus of the pressure-sensitive adhesive layer after photocuring.
[0082] Urethane (meth)acrylate is a compound having one or more urethane bonds and two or more (meth)acryloyl groups in one molecule, and preferably contains two or more urethane bonds in one molecule. Urethane (meth)acrylate having two or more urethane bonds can be obtained, for example, by reacting polyisocyanate with a (meth)acrylic compound having a hydroxy group, and the isocyanate group of the polyisocyanate and the hydroxy group of the (meth)acrylic compound bond to form a urethane bond.
[0083] The polyisocyanate may be any of aromatic polyisocyanate, alicyclic polyisocyanate, and alicyclic polyisocyanate. Among these, aromatic polyisocyanate and aliphatic polyisocyanate are preferred. As the aromatic polyisocyanate, tolylene diisocyanate (TDI) is particularly preferred. As the tolylene diisocyanate, either 2,4-tolylene diisocyanate or 2,6-tolylene diisocyanate may be used, or a mixture of both may be used. As the aliphatic polyisocyanate, hexamethylene diisocyanate (HDI) is particularly preferred.
[0084] The polyisocyanate may be a trifunctional isocyanate having a cyanuric acid skeleton. Examples of trifunctional isocyanates having a cyanuric acid skeleton include TDI trimer and HDI trimer. The polyisocyanate may have a biuret group or an allophanate group.
[0085] The polyisocyanate may be an isocyanate-terminated urethane prepolymer obtained by reacting a polyol with a polyisocyanate. The isocyanate-terminated urethane prepolymer may be a high molecular weight product obtained by reacting a high molecular weight polyol such as a polyester polyol, a polycarbonate polyol, or a polyether polyol with a polyisocyanate.
[0086] Examples of the (meth)acrylic compound having a hydroxy group include compounds having one hydroxy group and one (meth)acryloyl group, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxymethyl acrylamide, and hydroxyethyl acrylamide; and compounds having one hydroxy group and two or more (meth)acryloyl groups, such as pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, trimethylolpropane di(meth)acrylate, and isocyanuric acid di(meth)acrylate.
[0087] Among these, as the (meth)acrylic compound having a hydroxy group, a compound having one hydroxy group and two or more (meth)acryloyl groups is preferred, and specific examples thereof include compounds having a pentaerythritol skeleton such as pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate.
[0088] A urethane (meth)acrylate obtained by reacting a diisocyanate with a (meth)acrylic compound having one hydroxy group and two or more (meth)acryloyl groups in one molecule has two urethane bonds and four or more (meth)acryloyl groups in one molecule. The number of (meth)acryloyl groups in the urethane (meth)acrylate may be six or more, eight or more, or 12 or less, or 10 or less.
[0089] The urethane (meth)acrylate may be commercially available from Kyoeisha Chemical, Shin-Nakamura Chemical, Negami Chemical Industries, Mitsubishi Chemical, Daicel Allnex, Resonac, or the like.
[0090] From the viewpoints of compatibility with the acrylic base polymer and adjustment of the adhesive strength of the pressure-sensitive adhesive layer, the molecular weight of the urethane (meth)acrylate is preferably 300 to 10,000, more preferably 500 to 2,000, and may be 600 to 1,500 or 700 to 1,200. From the same viewpoints, the functional group equivalent (g / eq) of the (meth)acryloyl group of the urethane (meth)acrylate is preferably 80 to 5,000, more preferably 90 to 1,000, and even more preferably 100 to 300, and may be 110 to 250 or 120 to 200.
[0091] The content of the photocuring agent in the pressure-sensitive adhesive composition (total of the polyfunctional (meth)acrylate having no urethane bond and the urethane (meth)acrylate) is preferably 2 parts by weight or more, more preferably 3 parts by weight or more, even more preferably 5 to 7 parts by weight or more, and may be 8 parts by weight or more, or 10 parts by weight or more, relative to 100 parts by weight of the acrylic base polymer. By setting the amount of the photocuring agent within the above range, a reinforcing film is obtained that is easy to peel from the adherend before photocuring and that can be firmly adhered to the adherend after photocuring.
[0092] The greater the amount of photocuring agent, the weaker the adhesive strength between the adhesive and the adherend before photocuring, resulting in excellent peelability. On the other hand, if the amount of photocuring agent is excessively high, the adhesive tends to have low viscosity and insufficient adhesive strength and flexibility. Furthermore, the greater the amount of photocuring agent, the greater the storage modulus of the adhesive layer after photocuring, particularly at low temperatures, which tends to increase, making the reinforcing film and the adherend to which the reinforcing film is attached more likely to warp due to temperature changes. Furthermore, if the amount of photocuring agent is excessively high, the photocuring agent is likely to bleed out, and when the reinforcing film is peeled from the adherend, the bled-out components may transfer to the adherend, causing contamination. Therefore, the content of the photocuring agent is preferably 30 parts by weight or less, more preferably 25 parts by weight or less, and may be 20 parts by weight or less, 15 parts by weight or less, 12 parts by weight or less, or 10 parts by weight or less, per 100 parts by weight of the base polymer.
[0093] From the viewpoint of adjusting the adhesion between the pressure-sensitive adhesive layer and the adherend before and after photocuring and the storage modulus of the pressure-sensitive adhesive layer after photocuring within an appropriate range, the content of the polyfunctional (meth)acrylate not having a urethane bond is preferably 2 to 25 parts by weight, more preferably 3 to 20 parts by weight, and even more preferably 4 to 15 parts by weight, and may be 5 to 13 parts by weight, 6 to 12 parts by weight, or 7 to 10 parts by weight, relative to 100 parts by weight of the acrylic base polymer.
[0094] From the viewpoint of adjusting the adhesion between the pressure-sensitive adhesive layer and the adherend before and after photocuring and the storage modulus of the pressure-sensitive adhesive layer after photocuring within an appropriate range, the content of the urethane (meth)acrylate is preferably 0.03 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, and even more preferably 0.08 to 3 parts by weight, and may be 0.1 to 2.5 parts by weight or 0.15 to 2 parts by weight, relative to 100 parts by weight of the acrylic base polymer.
[0095] Urethane (meth)acrylates have low compatibility with acrylic-based polymers. Therefore, urethane (meth)acrylates tend to be unevenly distributed on the surface of the pressure-sensitive adhesive layer (near the adhesive interface with the adherend). Furthermore, polyfunctional (meth)acrylates with alkylene oxide chains have lower compatibility with acrylic-based polymers than polyfunctional (meth)acrylates without alkylene oxide chains. These photocuring agents tend to be unevenly distributed on the surface of the pressure-sensitive adhesive layer (near the adhesive interface with the adherend), and the photocuring agent unevenly distributed at the adhesive interface with the adherend is likely to form an adhesion-inhibiting layer (Weak Boundary Layer; WBL).
[0096] When a WBL is formed, the adhesive layer retains its bulk properties, such as storage modulus, while the liquid properties of the surface (adhesive interface) become stronger, tending to reduce the adhesive strength with the adherend. Therefore, the adhesive layer before photocuring is easy to peel from the adherend. When a WBL is formed on an adhesive layer in which the photocuring agent is unevenly distributed near the adhesive interface with the adherend, the curing reaction of the photocuring agent is likely to proceed near the adhesive interface where the photocuring agent is present at a high density, which tends to increase the cohesive force near the adhesive interface and increase the adhesive strength. Furthermore, when a WBL is formed, the increase in the storage modulus, a bulk property of the adhesive, tends to be suppressed after photocuring.
[0097] The inclusion of urethane (meth)acrylate as a photocuring agent tends to reduce the adhesive strength of the pressure-sensitive adhesive layer before photocuring. One possible reason for this is the promotion of WBL formation by the combined use of urethane (meth)acrylate and a polyfunctional (meth)acrylate that does not have a urethane bond.
[0098] In the adhesive layer after photocuring, the acrylic base polymer with a crosslinked structure and the polymer formed by curing the photocuring agent form a polymer network, and the cohesive force is increased by the interaction between the polar groups of the acrylic base polymer and the polar groups of the urethane (meth)acrylate, which is thought to increase the adhesive strength. Also, as mentioned above, if photocuring is performed while the WBL is formed, the cohesive force near the adhesive interface is likely to increase, which is thought to increase the adhesive strength at the interface and the high-temperature adhesive strength.
[0099] (Photopolymerization initiator) The photopolymerization initiator generates active species when irradiated with actinic rays, and promotes the curing reaction of the photocuring agent. As the photopolymerization initiator, it is preferable to use a photoradical polymerization initiator (photoradical generator).
[0100] The photoradical polymerization initiator is preferably one that generates radicals upon irradiation with visible light or ultraviolet light having a wavelength shorter than 450 nm, and examples thereof include hydroxyketones, benzyl dimethyl ketals, aminoketones, acylphosphine oxides, benzophenones, trichloromethyl group-containing triazine derivatives, etc. The photopolymerization initiators may be used alone or in combination of two or more.
[0101] The content of the photopolymerization initiator in the pressure-sensitive adhesive layer 2 is preferably 0.01 to 5 parts by weight, more preferably 0.02 to 3 parts by weight, and even more preferably 0.03 to 2 parts by weight, relative to 100 parts by weight of the base polymer. The content of the photopolymerization initiator in the pressure-sensitive adhesive layer 2 is preferably 0.02 to 20 parts by weight, more preferably 0.05 to 10 parts by weight, and even more preferably 0.1 to 7 parts by weight, relative to 100 parts by weight of the photocuring agent.
[0102] <Other ingredients> As described above, the photocurable pressure-sensitive adhesive composition constituting the pressure-sensitive adhesive layer 2 contains an acrylic-based polymer, a photocuring agent, and a photopolymerization initiator. The pressure-sensitive adhesive composition may contain components other than these.
[0103] For example, the pressure-sensitive adhesive composition may contain an oligomer having a lower molecular weight than the base polymer, for example, an acrylic oligomer having a weight-average molecular weight of about 1,000 to 30,000 in addition to the acrylic base polymer.
[0104] In addition to the above-mentioned components, the pressure-sensitive adhesive composition may contain additives such as a silane coupling agent, a tackifier, a crosslinking accelerator, a crosslinking retarder, a plasticizer, a softener, an antioxidant, an antidegradant, a filler, a colorant, an ultraviolet absorber, a surfactant, and an antistatic agent, within a range that does not impair the properties of the present invention.
[0105] Examples of crosslinking accelerators (crosslinking catalysts) include organometallic compounds such as organometallic complexes (chelates), compounds of metals with alkoxy groups, and compounds of metals with acyloxy groups; and tertiary amines. Organometallic compounds are preferred from the viewpoint of suppressing the progress of the crosslinking reaction in a solution state at room temperature and ensuring the pot life of the pressure-sensitive adhesive composition. Furthermore, organometallic compounds that are liquid at room temperature are preferred as crosslinking accelerators, as they are more likely to introduce a uniform crosslinked structure throughout the entire thickness direction of the pressure-sensitive adhesive layer. Examples of metals in organometallic compounds include iron, tin, aluminum, zirconium, zinc, titanium, lead, cobalt, and zinc.
[0106] Examples of crosslinking retarders include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate; β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone; and alcohols such as tert-butyl alcohol.
[0107] [Preparation of reinforcing film] A reinforcing film is obtained by laminating a photocurable pressure-sensitive adhesive layer 2 on a film substrate 1. The pressure-sensitive adhesive layer 2 may be formed directly on the film substrate 1, or a pressure-sensitive adhesive layer formed in sheet form on another substrate may be transferred onto the film substrate 1.
[0108] The pressure-sensitive adhesive composition is applied to a substrate by roll coating, kiss roll coating, gravure coating, reverse coating, roll brush, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, die coating, or the like, and the solvent is dried and removed as necessary to form a pressure-sensitive adhesive layer. A suitable drying method can be adopted as appropriate. The heating and drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and even more preferably 70°C to 170°C. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and even more preferably 10 seconds to 10 minutes.
[0109] When the pressure-sensitive adhesive composition contains a crosslinking agent, it is preferable to promote crosslinking by heating or aging simultaneously with or after drying of the solvent. The heating temperature and heating time are appropriately set depending on the type of crosslinking agent used, and crosslinking is usually achieved by heating in the range of 20°C to 160°C for about 1 minute to 7 days. The heating for drying and removing the solvent may also serve as the heating for crosslinking.
[0110] Even after the crosslinking structure is introduced into the polymer by the crosslinking agent, the photocuring agent remains unreacted. Therefore, the pressure-sensitive adhesive layer 2 is made of a photocurable pressure-sensitive adhesive composition containing an acrylic-based polymer with a crosslinking structure introduced therein, a photocuring agent, and a photopolymerization initiator. When the pressure-sensitive adhesive layer 2 is formed on the film substrate 1, it is preferable to apply a release liner 5 onto the pressure-sensitive adhesive layer 2 for purposes such as protecting the pressure-sensitive adhesive layer 2. Crosslinking may be carried out after the release liner 5 is applied onto the pressure-sensitive adhesive layer 2.
[0111] When the pressure-sensitive adhesive layer 2 is formed on another substrate, the reinforcing film is obtained by transferring the pressure-sensitive adhesive layer 2 onto the film substrate 1 after drying the solvent. The substrate used to form the pressure-sensitive adhesive layer may be used as the release liner 5 as is.
[0112] As the release liner 5, a plastic film such as polyethylene, polypropylene, polyethylene terephthalate, or polyester film is preferably used. The thickness of the release liner is typically 3 to 200 μm, preferably about 10 to 100 μm. The surface of the release liner 5 that comes into contact with the pressure-sensitive adhesive layer 2 is preferably treated with a release agent such as a silicone-based, fluorine-based, long-chain alkyl-based, or fatty acid amide-based release agent, or with silica powder or the like. By treating the surface of the release liner 5 with a release treatment, when the release liner 5 is peeled from the film substrate 1, peeling occurs at the interface between the pressure-sensitive adhesive layer 2 and the release liner 5, maintaining the pressure-sensitive adhesive layer 2 adhered to the film substrate 1. The release liner 5 may be antistatically treated on either or both of the release-treated and untreated surfaces. By treating the release liner 5 with an antistatic treatment, charging when the release liner is peeled from the pressure-sensitive adhesive layer can be suppressed.
[0113] [Characteristics of the reinforcing film and use of the reinforcing film] The reinforced film of the present invention is used by being attached to a device or a device component. The reinforced film 10 has a pressure-sensitive adhesive layer 2 fixed to a film substrate 1, and has low adhesive strength to the adherend after being attached to the adherend and before being photocured. Therefore, the reinforced film can be easily peeled from the adherend before being photocured.
[0114] The adherend to which the reinforced film is attached is not particularly limited, and examples thereof include various electronic devices, optical devices, and components thereof. In one embodiment, the reinforced film is attached to the surface of a foldable flexible device. The foldable device has a hinge portion and can be folded around this hinge portion. The folding angle can be set arbitrarily, and the device may be bent (folded) by 180°. When the device is a display device, the reinforced film may be attached to the surface on the screen side, or to the back side (housing). A flexible device that is configured to be bendable at a predetermined location such as a hinge portion repeatedly bends and stretches at the same location when in use.
[0115] The reinforcing film may be attached to the entire surface of the adherend, or may be selectively attached only to the areas requiring reinforcement (reinforcement target areas). After the reinforcing film is attached to the entire areas requiring reinforcement (reinforcement target areas) and areas not requiring reinforcement (non-reinforcement target areas), the reinforcing film is cut and peeled off from the non-reinforcement target areas, thereby producing a device in which the reinforcing film is attached only to the areas requiring reinforcement. Before the adhesive is photocured, the reinforcing film is temporarily attached to the surface of the adherend, and because its adhesive strength is weak, the reinforcing film can be easily peeled off and removed from the surface of the adherend.
[0116] By laminating a reinforcing film, appropriate rigidity is imparted, which is expected to improve the handleability and prevent breakage of thin members such as flexible devices. When a reinforcing film is laminated to a work-in-progress in the device manufacturing process, the reinforcing film may be laminated to a large-sized work-in-progress before it is cut to the product size. The reinforcing film may also be laminated roll-to-roll to the mother roll of a device manufactured by a roll-to-roll process.
[0117] For example, a reinforcing film is laminated to a mother roll of a device or a work-in-progress thereof using a roll-to-roll method, and then the mother roll to which the reinforcing film is laminated is cut and separated into individual products. Only the reinforcing film is cut using a half cut, and the reinforcing film in the non-reinforced area is peeled off, thereby obtaining a device in which the reinforcing film is laminated to the area to be reinforced. The cutting method is not particularly limited, and any appropriate cutting method such as a rotary cutter, a push blade (e.g., a Thomson blade), or a laser cutter can be used.
[0118] Before laminating the reinforcing film, the surface of the adherend may be subjected to an activation treatment for the purpose of cleaning, etc. Examples of surface activation treatment include plasma treatment, corona treatment, and glow discharge treatment.
[0119] From the viewpoints of facilitating peeling from the adherend and preventing adhesive residue on the adherend after peeling of the reinforcing film, the adhesive strength (initial adhesive strength) between the pressure-sensitive adhesive layer 2 and the adherend before photocuring is preferably 0.6 N / 25 mm or less, more preferably 0.5 N / 25 mm or less, even more preferably 0.4 N / 25 mm or less, and may be 0.3 N / 25 mm or less, 0.25 N / 25 mm or less, or 0.2 N / 25 mm or less. From the viewpoint of preventing peeling of the reinforcing film during storage or handling, the adhesive strength between the pressure-sensitive adhesive layer 2 and the adherend before photocuring is preferably 0.005 N / 25 mm or more, more preferably 0.01 N / 25 mm or more.
[0120] Adhesion strength is determined by a peel test using a polyimide film as the adherend at a tensile speed of 300 mm / min and a peel angle of 180°. Unless otherwise specified, adhesion strength is measured at 25°C. The adhesion strength between the pressure-sensitive adhesive layer and the adherend before photocuring is measured using a sample that has been left to stand at 25°C for 30 minutes after lamination.
[0121] The shear storage modulus of the pressure-sensitive adhesive layer 2 at a temperature of 25°C before photocuring (hereinafter simply referred to as "storage modulus") is preferably 15 kPa or more, more preferably 20 kPa or more, and may be 25 kPa or more or 30 kPa or more. The greater the storage modulus of the pressure-sensitive adhesive layer at room temperature before photocuring, the more improved the cutting processability becomes, and the more likely it is that adhesive residue on the adherend when the reinforcing film is peeled from the adherend is suppressed.
[0122] On the other hand, if the storage modulus of the pressure-sensitive adhesive layer at room temperature before photocuring is excessively large, the storage modulus of the pressure-sensitive adhesive layer after photocuring also tends to be large, which may result in insufficient adhesion to the adherend or impact resistance. Furthermore, if the storage modulus of the pressure-sensitive adhesive layer before photocuring is large, the storage modulus of the pressure-sensitive adhesive layer after photocuring also tends to be large, so that when applied to a foldable device, the pressure-sensitive adhesive layer cannot absorb the strain at and around the bending point, and the reinforcing film is easily peeled off from the device. Therefore, the storage modulus of the pressure-sensitive adhesive layer at a temperature of 25 ° C. before photocuring is preferably 50 kPa or less, more preferably 45 kPa or less, and even more preferably 40 kPa or less.
[0123] The storage modulus of the pressure-sensitive adhesive layer is determined by reading the value at a predetermined temperature when measured at a temperature rise rate of 5°C / min in the range of -70 to 200°C under conditions of a frequency of 1 Hz in accordance with the method described in JIS K7244-1 "Plastics - Testing methods for dynamic mechanical properties." In this specification, unless otherwise specified, the storage modulus is the value at a temperature of 25°C.
[0124] After laminating the reinforcing film to the adherend, the pressure-sensitive adhesive layer 2 is irradiated with actinic rays to photocure the pressure-sensitive adhesive layer. Ultraviolet rays are preferred as the actinic rays. The irradiation intensity and irradiation time of the actinic rays may be appropriately set depending on the composition and thickness of the pressure-sensitive adhesive layer 2. The pressure-sensitive adhesive layer 2 may be irradiated with actinic rays from either the film substrate 1 side or the adherend side, or may be irradiated with actinic rays from both sides.
[0125] When the pressure-sensitive adhesive layer 2 is photocured, the photocuring agent undergoes a curing reaction, increasing the adhesive strength with the adherend. From the viewpoint of adhesive reliability during practical use of the device, the adhesive strength F1 between the pressure-sensitive adhesive layer and the adherend after photocuring at a temperature of 25°C is preferably 3 N / 25 mm or more, more preferably 5 N / 25 mm or more, and may be 7 N / 25 mm or more, 9 N / 25 mm or more, or 10 N / 25 mm or more. The adhesive strength F1 between the pressure-sensitive adhesive layer and the adherend after photocuring is preferably 10 times or more, more preferably 15 times or more, even more preferably 20 times or more, and may be 30 times or more, or 50 times or more, the adhesive strength F0 between the pressure-sensitive adhesive layer and the adherend before photocuring.
[0126] The adhesive strength F2 between the pressure-sensitive adhesive layer and the adherend after photocuring at a temperature of 85°C is preferably 1 N / 25 mm or more, more preferably 2 N / 25 mm or more, even more preferably 3 N / 25 mm or more, and may be 4 N / 25 mm or more, 5 N / 25 mm or more, or 6 N / 25 mm or more.
[0127] As described above, by including urethane (meth)acrylate as a photocuring agent, the cohesive force at the adhesive interface tends to be increased, and the adhesive strength of the pressure-sensitive adhesive layer after photocuring tends to be increased.
[0128] From the viewpoint of realizing high adhesive strength with the adherend after photocuring, the storage modulus of the pressure-sensitive adhesive layer at a temperature of 25°C after photocuring is preferably 40 kPa or more, more preferably 50 kPa or more, and may be 55 kPa or more or 60 kPa or more. On the other hand, if the storage modulus of the pressure-sensitive adhesive layer after photocuring is excessively high, the adhesive strength with respect to the adherend and the shock-absorbing effect (cushioning properties) tend to decrease. Furthermore, if the storage modulus of the pressure-sensitive adhesive layer after photocuring is excessively high, when applied to a foldable device, the reinforcing film is likely to peel off from the device at and around the bending points. Therefore, the storage modulus of the pressure-sensitive adhesive layer at a temperature of 25°C after photocuring is preferably 100 kPa or less, more preferably 90 kPa or less, and even more preferably 80 kPa or less.
[0129] The smaller the amount of crosslinking agent and the amount of photocuring agent, the smaller the storage modulus of the pressure-sensitive adhesive layer after photocuring tends to be, and the smaller the amount of photocuring agent, the smaller the increase in the storage modulus of the pressure-sensitive adhesive layer due to photocuring tends to be. Furthermore, by including a polyfunctional (meth)acrylate having no urethane bond and a urethane (meth)acrylate as the photocuring agent, the adhesive strength to the adherend tends to be increased while suppressing the increase in the storage modulus of the pressure-sensitive adhesive layer due to photocuring.
[0130] The storage modulus of the pressure-sensitive adhesive layer after photocuring at a temperature of -40°C is preferably 1000 kPa or less, more preferably 900 kPa or less, and may be 800 kPa or less, 750 Pa or less, or 700 kPa or less. The smaller the storage modulus at -40°C, the smaller the change in storage modulus with temperature change, and the more likely it is that warping of the reinforcing film and the adherend to which the reinforcing film is bonded after a temperature cycle test will be suppressed. The storage modulus of the pressure-sensitive adhesive layer after photocuring at a temperature of -40°C may be 300 kPa or more, 400 kPa or more, 450 kPa or more, or 500 kPa or more.
[0131] From the viewpoints of increasing adhesive strength at high temperatures and ensuring the ability of the pressure-sensitive adhesive layer to follow deformations such as bending of the adherend, the storage modulus of the pressure-sensitive adhesive layer after photocuring at a temperature of 85°C is preferably 40 to 100 kPa, more preferably 50 to 90 kPa, and may be 55 to 85 kPa or 60 to 80 kPa.
[0132] The difference between the storage modulus of the pressure-sensitive adhesive layer at -40°C and that at 85°C after photocuring is preferably 900 kPa or less, more preferably 800 kPa or less, and even more preferably 700 kPa or less. The storage modulus of the pressure-sensitive adhesive layer at -40°C after photocuring is preferably 10 times or less, more preferably 9.5 times or less, and even more preferably 9 times or less, the storage modulus at 85°C. The smaller the difference in storage modulus between low temperature (-40°C) and high temperature (85°C), the more likely it is that warping of the reinforced film and the adherend to which the reinforced film is bonded will be suppressed after a temperature cycle test.
[0133] As with the storage modulus at room temperature (25°C), the lower the amount of crosslinker and the amount of photocuring agent, the lower the storage modulus of the photocured adhesive layer at low temperatures (-40°C) and high temperatures (85°C). Furthermore, by including a polyfunctional (meth)acrylate and a urethane (meth)acrylate without a urethane bond as the photocuring agent, the adhesive strength to the adherend tends to be increased while suppressing an increase in the storage modulus of the photocured adhesive layer at low temperatures. Furthermore, when the main monomer of the acrylic base polymer is (meth)acrylic acid C, 6-9 It is an alkyl ester and contains (meth)acrylic acid C as a monomer component. 6-9 Alkyl ester plus (meth)acrylic acid C 10-20 By including an alkyl ester, the temperature dependence of the storage modulus of the pressure-sensitive adhesive layer after photocuring tends to be smaller.
[0134] The difference between the storage modulus of the photocured pressure-sensitive adhesive layer at 25°C and the storage modulus at 85°C is preferably 50 kPa or less, more preferably 30 kPa or less, even more preferably 20 kPa or less, and may be 15 kPa or less, 10 kPa or less, or 5 kPa or less. The storage modulus of the photocured pressure-sensitive adhesive layer at 85°C may be smaller than the storage modulus at 25°C. The storage modulus of the photocured pressure-sensitive adhesive layer at 85°C is preferably 0.8 to 1.2 times, more preferably 0.85 to 1.15 times, and may be 0.9 to 1.1 times, 0.93 to 1.07 times, or 0.95 to 1.05 times the storage modulus at 25°C.
[0135] The smaller the difference in storage modulus between room temperature (25°C) and high temperature (85°C), the more likely it is that the warping of the reinforced film and the substrate to which the reinforced film is attached after a temperature cycle test will be suppressed. Furthermore, when the reinforced film is applied to a foldable device, peeling of the reinforced film due to deformation at and near the bending point (hinge) tends to be suppressed. The lower the glass transition temperature of the base polymer, the lower the temperature-dependent region of viscoelasticity (plateau region) shifts to lower temperatures, which tends to reduce the difference in storage modulus between room temperature and high temperatures.
[0136] By laminating a reinforcing film, the adherend is given an appropriate degree of rigidity and stress is alleviated and dispersed, thereby suppressing various defects that may occur during the manufacturing process, improving production efficiency, and improving yield.
[0137] The reinforcing film of the present invention has a photocurable pressure-sensitive adhesive layer 2, and the timing of curing can be set as desired. Before the pressure-sensitive adhesive layer is photocured, the reinforcing film of the present invention has low adhesive strength even to surface-treated adherends, making it easy to peel from the adherend and easy to rework in the event of lamination or bonding defects. Furthermore, processing such as selectively removing the reinforcing film from areas not to be reinforced is also easy.
[0138] After photocuring, the pressure-sensitive adhesive layer exhibits high adhesive strength to the adherend, making the reinforced film less likely to peel off from the device surface. In a device with a reinforced film, in which the reinforced film of the present invention is bonded to a flexible device using a resin substrate, the reinforced film is less likely to peel off at the bending points, even when the device is repeatedly bent. Furthermore, because the storage modulus of the pressure-sensitive adhesive layer changes little with temperature changes, warping of the device is suppressed, allowing the display characteristics to be maintained, and the reinforced film is less likely to peel off with temperature changes, resulting in excellent reliability. [Example]
[0139] The present invention will be further explained below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0140] [Preparation of base polymer] <Polymer A> A reaction vessel equipped with a thermometer, stirrer, reflux condenser, and nitrogen gas inlet tube was charged with 20 parts by weight of butyl acrylate (BA), 70 parts by weight of 2-ethylhexyl acrylate (2EHA), 8 parts by weight of lauryl acrylate (LA), 1 part by weight of 4-hydroxybutyl acrylate (4HBA), and 1 part by weight of N-vinyl-2-pyrrolidone (NVP), 0.1 parts by weight of azobisisobutyronitrile (AIBN) as a thermal polymerization initiator, and 233 parts by weight of ethyl acetate as a solvent. Nitrogen gas was introduced and the mixture was stirred for about 1 hour while nitrogen substitution was performed. The mixture was then heated to 60°C and reacted for 7 hours to obtain a solution of acrylic polymer A with a weight-average molecular weight of 1.8 million.
[0141] <Polymers B to D> The amounts of monomers charged were changed as shown in Table 1, and the amount of thermal polymerization initiator (AIBN) was changed to 0.2 parts by weight in the polymerization of polymers B and D. Solutions of polymers B to D were obtained in the same manner as in the polymerization of polymer A except for these changes.
[0142] The monomer ratios used for acrylic polymers A to D and the weight average molecular weights (Mw) of the polymers are listed in Table 1. The weight average molecular weights (polystyrene equivalent) were measured using GPC ("HLC-8220GPC" manufactured by Tosoh) under the following conditions. Sample concentration: 0.2 wt% (tetrahydrofuran solution) Sample injection volume: 10 μL Eluent:THF Flow rate: 0.6mL / min Measurement temperature: 40℃ Sample column: TSKguardcolumn SuperHZ-H (1 column) + TSKgel SuperHZM-H (2 columns) Reference column: TSKgel SuperH-RC (1 column)
[0143] In Table 1, the monomers are described by the following abbreviations. BA: butyl acrylate 2EHA: 2-ethylhexyl acrylate NOAA: n-octyl acrylate LA: Lauryl acrylate 2HEA: 2-hydroxyethyl acrylate 4HBA: 4-hydroxybutyl acrylate AA: Acrylic acid NVP: N-vinyl-2-pyrrolidone
[0144] [Table 1]
[0145] [Preparation of reinforcing film] <Preparation of Pressure-Sensitive Adhesive Composition> A crosslinking agent, a multifunctional acrylate (having no urethane bond) and a urethane acrylate as photocuring agents, and a photopolymerization initiator were added to a solution of an acrylic polymer and mixed uniformly to prepare the pressure-sensitive adhesive compositions shown in Table 2.
[0146] As a photopolymerization initiator, 0.3 parts by weight of "Omnirad 651" manufactured by IGM Resins was added per 100 parts by weight of the solid content of the acrylic polymer. The crosslinking agent and photocuring agent (multifunctional acrylate and urethane acrylate) were added in the amounts shown in Table 2. The amounts added in Table 2 are the amounts (parts by weight of solid content) per 100 parts by weight of the acrylic polymer. Details of the crosslinking agent and photocuring agent are as follows:
[0147] (Crosslinking agent) C / HX: Hexamethylene diisocyanate isocyanurate (Tosoh's "Coronate HX") T / C: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (tetrafunctional epoxy compound, "Tetrad C" manufactured by Mitsubishi Gas Chemical Company)
[0148] (multifunctional acrylate) A200: Shin-Nakamura Chemical Co., Ltd. "NK Ester A200" (polyethylene glycol #200 (n=4) diacrylate; molecular weight 308, functional group equivalent weight 154 g / eq) M350: Trimethylolpropane EO-modified (n=1) triacrylate (Toagosei "Aronix M-350", functional group equivalent weight 143g / eq) ADPHE: Ethoxylated dipentaerythritol polyacrylate ("NK Ester A-DPH-12E" manufactured by Shin-Nakamura Chemical Co., Ltd., functional group equivalent weight approximately 200 g / eq)
[0149] (urethane acrylate) UA306: Pentaerythritol triacrylate-tolylene diisocyanate adduct (Kyoeisha Chemical Company, "UA-306T", functional group equivalent: 128g / eq) UA510: Dipentaerythritol pentaacrylate hexamethylene diisocyanate adduct (Kyoeisha Chemical Co., Ltd. "UA-510H", functional group equivalent: 181g / eq) UF-X9-83: Polycarbonate skeleton-containing urethane acrylate (Kyoeisha Chemical Company, "UF-X9-83", functional groups 2-3, weight-average molecular weight 8400)
[0150] <Application of adhesive solution and crosslinking> The above-mentioned adhesive composition was applied to a 50 μm-thick polyethylene terephthalate film substrate ("Diafoil T100" manufactured by Mitsubishi Chemical Corporation) that had not been surface-treated, using a fountain roll, so that the dried thickness would be 15 μm. After drying at 130°C for 1 minute to remove the solvent, the release-treated surface of a release liner (a 25 μm-thick polyethylene terephthalate film whose surface had been treated with silicone release) was attached to the adhesive-coated surface. Subsequently, an aging treatment was performed for 4 days in an atmosphere at 25°C to promote crosslinking, resulting in a reinforced film in which the adhesive sheet was firmly laminated onto the film substrate and the release liner was temporarily attached thereto.
[0151] [evaluation] <Adhesion strength to polyimide film> (Adhesive strength of adhesive layer before photocuring) A 25 μm-thick polyimide film (UBE "Upilex 25S") was attached to a glass plate using double-sided adhesive tape (Nitto Denko "No. 531") to obtain a polyimide film substrate for measurement. A 25 mm wide x 100 mm long piece of reinforcing film was cut out, and the release liner was removed from the surface. The film was then attached to the polyimide film substrate for measurement using a hand roller.
[0152] After leaving this sample at 25°C for 30 minutes, the edge of the film substrate of the reinforcing film was held with a chuck and a 180° peel test was performed at a pulling speed of 300 mm / min to measure the peel strength (adhesion strength F0 of the reinforcing film to the polyimide film).
[0153] (Adhesive strength of adhesive layer after photocuring) After laminating the reinforcing film to the polyimide film substrate for measurement, an LED light source with a wavelength of 365 nm was used from the reinforcing film side (film substrate side) with an integrated light intensity of 4000 mJ / cm 2The adhesive layer was photocured by irradiating it with ultraviolet light of 1000 kJ / cm². Using this test sample, adhesive strength F1 was measured by a 180° peel test at a temperature of 25°C in the same manner as above. Furthermore, the test sample after photocuring of the adhesive layer was stored in an oven at a temperature of 85°C for 5 minutes, and then a 180° peel test was performed in an environment at a temperature of 85°C to measure adhesive strength F2.
[0154] <Storage modulus> The adhesive composition was applied to the release liner and crosslinked in the same manner as above to prepare an adhesive sheet (before photocuring). A release liner was attached to the surface of the adhesive layer of the adhesive sheet before photocuring to shield it from oxygen, and the adhesive sheet was exposed to 4000 mJ / cm 2 of light from a 365 nm LED lamp. 2 The adhesive sheet before and after photocuring were laminated to prepare a measurement sample with a thickness of approximately 1.5 mm, and dynamic viscoelasticity measurements were performed under the following conditions using a rotational rheometer (TA Instruments "Discovery-HR2") to read the shear storage modulus G' values at -40°C, 25°C, and 85°C. (Measurement conditions) Deformation mode: Torsion Measurement frequency: 1Hz Heating rate: 5°C / min Measurement temperature: -70~200℃ Shape: Parallel plate 8.0mmφ
[0155] <Temperature cycle test> The release liner was peeled off from the surface of the reinforcement film, and the film was then laminated to a 25 μm thick polyimide film (UBE's "Upilex 25S") using a hand roller. After that, an LED light source with a wavelength of 365 nm was used from the reinforcement film side (film substrate side) to irradiate the film with an integrated light intensity of 4000 mJ / cm. 2The adhesive layer was photocured by irradiating it with ultraviolet light. This test sample was cut into a size of 20 mm x 100 mm and subjected to a temperature cycle test. The temperature cycle was carried out 200 times, with the sample being placed in a test chamber, held at -40°C for 30 minutes, heated to 85°C (6.25°C / min), held at 85°C for 30 minutes, and cooled to -40°C (6.25°C / min). After the temperature cycle test, the sample was placed on a horizontal table with the long sides touching, and the amount of curl at the edges was measured.
[0156] <Stainability of adherends> The release liner was peeled off from the surface of a 25mm wide x 100mm long piece of reinforced film, and the piece was then laminated to a polyimide film substrate for measurement using a hand roller. After leaving the film at 25°C for 30 minutes or 24 hours, the reinforced film was peeled off from the polyimide film, and the surface of the polyimide film was visually inspected under fluorescent light to check for contamination. The contamination of the adherend was evaluated according to the following criteria. A: No contamination was observed on the sample that was peeled off after being left to stand for 24 hours. B: Contamination was observed in the sample peeled off after leaving it for 24 hours, but not in the sample peeled off after leaving it for 30 minutes. C: Contamination was observed on the sample that peeled off after being left standing for 30 minutes.
[0157] Table 2 shows the composition of the adhesive for each reinforcing film (type of base polymer, amount of crosslinking agent added, type and amount of photocuring agent added), as well as the evaluation results.
[0158] [Table 2]
[0159] Comparative Example 1, which used a pressure-sensitive adhesive composition containing 100 parts by weight of polymer A and 2 parts by weight of multifunctional acrylate (M350) as a photocuring agent, had an adhesive strength F0 to polyimide film of more than 1 N / 25 mm, demonstrating a large initial adhesive strength. Comparative Example 2, which used 0.15 parts by weight of urethane acrylate (UA306) as a photocuring agent, demonstrated an even greater initial adhesive strength than Comparative Example 1.
[0160] Example 1, which blended 2 parts by weight of a multifunctional acrylate (M350) and 0.15 parts by weight of a urethane acrylate (UA306) as a photocuring agent with 100 parts by weight of Polymer A, had a smaller initial adhesive strength F0 and showed a larger adhesive strength after photocuring than Comparative Examples 1 and 2. Furthermore, in Example 1, the storage modulus of the adhesive after photocuring was 60 kPa or less, and it had flexibility suitable for use in foldable devices, etc.
[0161] In Examples 2 to 4, in which the amount of polyfunctional acrylate was increased compared to Example 1, there was a tendency for the initial adhesive strength F0 to decrease and the adhesive strength F1 after photocuring to increase as the amount of polyfunctional acrylate increased. On the other hand, in Example 5, in which the amount of polyfunctional acrylate was further increased compared to Example 4, the adhesive strength after photocuring was smaller than in Example 4. In Comparative Example 3, in which the amount of polyfunctional acrylate was further increased, the adhesive strength after photocuring was even smaller. Furthermore, in Comparative Example 3, contamination of the adherend was observed when the reinforcing film was peeled off before the pressure-sensitive adhesive was photocured.
[0162] In Examples 1 to 5 and Comparative Example 3, as the amount of multifunctional acrylate increased, the storage modulus of the pressure-sensitive adhesive layer before photocuring tended to decrease and the storage modulus of the pressure-sensitive adhesive after photocuring tended to increase, with the increase in storage modulus at low temperature (-40°C) being particularly notable. As the storage modulus of the pressure-sensitive adhesive layer after photocuring increased at low temperatures, the difference between the storage modulus at low temperature (-40°C) and high temperature (85°C) increased, and the sample tended to curl more after the temperature cycle test.
[0163] Examples 14 and 15, in which the type of multifunctional acrylate was changed, showed small initial adhesive strength F0 to the adherend and large adhesive strength F2 at high temperatures of the pressure-sensitive adhesive layer after photocuring, similar to Example 4. In Example 15, the amount of curl of the sample after the temperature cycle test was equivalent to that of Example 4, and in Example 14, which used a bifunctional acrylate (A200), the storage modulus at each temperature was smaller than in Examples 4 and 15, and curl of the sample after the temperature cycle test was reduced.
[0164] In Examples 6 to 8, in which the amount of urethane acrylate was increased compared to Example 4, the initial adhesive strength F0 to the adherend was small, the adhesive strength F2 at high temperatures of the pressure-sensitive adhesive layer after photocuring was large, and the storage modulus was low, similar to Example 4, and the curling of the sample after the temperature cycle test was reduced. In Examples 6 to 8, the adhesive strength F2 at high temperatures tended to increase with an increase in the amount of urethane acrylate. Furthermore, the storage modulus of the pressure-sensitive adhesive layer after photocuring tended to increase with an increase in the amount of urethane acrylate, but the increase in the storage modulus was slight, and no difference was observed in the amount of curling of the sample after the temperature cycle test.
[0165] Examples 12 and 13, which used a urethane acrylate different from that of Example 4, showed a small initial adhesive strength F0, and a large adhesive strength F2 at high temperatures of the adhesive layer after photocuring, similar to Example 4.
[0166] Example 12, which used a decafunctional urethane acrylate (UA510), had a smaller initial adhesive strength F0 than Example 4, which used a hexafunctional urethane acrylate (UA306), and the adhesive strength F2 at high temperatures after photocuring was greater than Example 4. On the other hand, Example 13, which used a high molecular weight urethane acrylate (UF-X9-83), had a larger F0 and a smaller F2 than Examples 4 and 12. These results show that the greater the number of functional groups in the urethane acrylate and the smaller the functional group equivalent weight, the greater the effect of reducing the initial adhesive strength and improving the adhesive strength.
[0167] Comparing Example 1 with Examples 9 to 11, it was found that the greater the amount of crosslinker, the smaller the adhesive strength of the pressure-sensitive adhesive layer before and after photocuring and the larger the storage modulus tended to be, and the greater the curl amount of the sample after the temperature cycle test tended to be as the storage modulus increased.
[0168] In Comparative Example 4, which used polymer B having a composition of 2EHA / 2HEA=96 / 4 as the base polymer of the adhesive, the adhesive layer after photocuring had a smaller adhesive strength F2 at high temperatures than in Example 4. Furthermore, in Comparative Example 4, the storage modulus of the adhesive layer after photocuring was large at low temperatures, and therefore the difference in storage modulus between low temperature and high temperature (85°C) was large, resulting in significant curling of the sample after the temperature cycle test.
[0169] In Comparative Example 4, which used polymer B having a composition of 2EHA / 2HEA=96 / 4 as the base polymer of the adhesive, the adhesive layer after photocuring had a smaller adhesive strength F2 at high temperatures than in Example 4. Furthermore, in Comparative Example 4, the adhesive layer after photocuring had a large storage modulus at low temperatures, and therefore the difference between the storage modulus at low and high temperatures (85°C) was large, resulting in significant curling of the sample after the temperature cycle test.
[0170] Comparative Example 5, which used polymer C having a composition of BA / NOAA / 4HBA=20 / 70 / 10 as the base polymer of the adhesive, showed an even smaller adhesive strength F2 at high temperatures than Comparative Example 4. Furthermore, in Comparative Example 5, the storage modulus of the adhesive layer after photocuring at low temperatures was smaller than in Comparative Example 4, but the low-temperature storage modulus and the difference between the low-temperature and high-temperature storage moduli were larger than in Example 4, and the curl of the sample after the temperature cycle test was also larger than in Example 1.
[0171] In Comparative Example 6, in which polymer D having a composition of BA / AA=95 / 5 was used as the base polymer of the adhesive and the amount of multifunctional acrylate was 30 parts by weight, the adhesive layer after photocuring had a small adhesive strength F2 at high temperatures and the sample curled significantly after the temperature cycle test.
[0172] From these results, it is considered that acrylic acid C is used as the monomer component of the base polymer. 12 It was found that by using polymer A containing lauryl acrylate, an alkyl ester, and by using a multifunctional (meth)acrylate without a urethane bond and a urethane (meth)acrylate as a photocuring agent, the adhesive layer after photocuring can achieve both high adhesive strength at high temperatures and reduced curling during temperature cycling due to a low storage modulus. [Explanation of symbols]
[0173] 1. Film substrate 2. Adhesive layer 10 Reinforcement film 5 Release liner 20 Adherent
Claims
1. The adhesive tape comprises a film substrate and a pressure-sensitive adhesive layer fixedly laminated on one main surface of the film substrate, the pressure-sensitive adhesive layer is made of a photocurable composition including an acrylic base polymer, a photocuring agent having two or more photopolymerizable functional groups, and a photopolymerization initiator; The acrylic base polymer contains, as a monomer component, (meth)acrylic acid C having an alkyl group with 6 to 9 carbon atoms. 6-9 Alkyl ester, (meth)acrylic acid C having an alkyl group with 10 to 20 carbon atoms 10-20 The (meth)acrylic acid C is a monomer mixture containing at least one monomer selected from the group consisting of an alkyl ester, a hydroxyl group-containing monomer, and a carboxyl group-containing monomer, and the (meth)acrylic acid C is a monomer mixture containing at least one monomer selected from the group consisting of an alkyl ester, a hydroxyl group-containing monomer, and a carboxyl group-containing monomer, 6-9 The amount of alkyl ester is 40 parts by weight or more, A crosslinked structure is introduced into the acrylic base polymer, The photocurable composition contains, as the photocuring agent, 2 to 25 parts by weight of a polyfunctional (meth)acrylate having no urethane bond relative to 100 parts by weight of the acrylic base polymer; and 0.03 to 5 parts by weight of a urethane (meth)acrylate relative to 100 parts by weight of the acrylic base polymer. Reinforcement film.
2. The reinforcing film according to claim 1, wherein a crosslinked structure is introduced into the acrylic base polymer using 0.05 to 1.0 parts by weight of a crosslinking agent relative to 100 parts by weight of the polymer.
3. The reinforced film according to claim 2 , wherein the crosslinking agent is an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent.
4. (Meth)acrylic acid C relative to 100 parts by weight of the total amount of the monomer components of the acrylic base polymer 10-20 The reinforced film of claim 1, wherein the amount of the alkyl ester is from 1 to 40 parts by weight.
5. The reinforcing film according to claim 1, wherein the polyfunctional (meth)acrylate has a functional group equivalent of a (meth)acryloyl group of 80 to 500 g / eq.
6. The reinforcing film according to claim 1, wherein the urethane (meth)acrylate has a functional group equivalent of a (meth)acryloyl group of 80 to 5000 g / eq.
7. The reinforcing film according to claim 1 , wherein the urethane (meth)acrylate has four or more (meth)acryloyl groups in one molecule.
8. The pressure-sensitive adhesive layer is Before photocuring, the adhesive strength F to the polyimide film at a temperature of 25° C. 0 is 0.6 N / 25 mm or less, After photocuring, the adhesive strength F to the polyimide film in an environment at a temperature of 25° C. 1 Adhesive strength F at 3.0 N / 25 mm or more and at a temperature of 85°C 2 is 1.0N / 25mm or more, The reinforced film according to claim 1 .
9. The reinforcing film according to claim 1 , wherein the pressure-sensitive adhesive layer has a shear storage modulus of 100 kPa or less at a temperature of 25° C. after photocuring.
10. The reinforcing film according to claim 1, wherein the pressure-sensitive adhesive layer has a shear storage modulus of 1000 kPa or less at a temperature of −40° C. after photocuring.
11. A method for manufacturing a device having a reinforcing film bonded to a surface thereof, comprising the steps of: After the pressure-sensitive adhesive layer of the reinforcing film according to any one of claims 1 to 10 is temporarily attached to the surface of an adherend, A device manufacturing method comprising: irradiating the pressure-sensitive adhesive layer with active light rays to photocure the pressure-sensitive adhesive layer, thereby increasing the adhesive strength between the reinforcing film and the adherend.
12. The method for manufacturing a device described in claim 11, wherein after the reinforcing film is temporarily attached to the adherend, and before the adhesive layer is photocured, the reinforcing film temporarily attached to the adherend is cut, and the reinforcing film is peeled off and removed from a portion of the adherend.
13. The method for manufacturing a device according to claim 11 , wherein the adherend is a foldable image display element.
14. A reinforcing method for bonding a reinforcing film to a surface of an adherend, comprising the steps of: The pressure-sensitive adhesive layer of the reinforcing film according to any one of claims 1 to 10 is temporarily attached to a surface of an adherend, The reinforcing method includes irradiating the pressure-sensitive adhesive layer with active light rays to photocure the pressure-sensitive adhesive layer, thereby increasing the adhesive strength between the reinforcing film and the adherend.
Citation Information
Patent Citations
Reinforcing film, device with reinforcing film, and method for manufacturing the same
WO2022050009A1